Pendampingan Pengasuhan Ibu dengan Anak Usia Pra Sekolah melalui Kelompok Bright Mom di TK ABA Bangsalsari - Haryanti, Dwi Yunita; Suryaningsih, Yeni; Wijaya, Risty Amalia Putri; Adilillah, Raya Lintang; Maghrobi, Nurul Al; Laksanawati, Wijha (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The use of gadgets is increasing very rapidly among preschoolers which can lead to health problems and technology addiction. The dual role of a mother is one of the factors that influences the mother's attitude towards gadgets in children. This community service aims to provide parenting assistance by forming a group of wise mothers in the digital era. The method used is by planning, forming groups and providing materials and assistance. The result of this assistance is an increase in the mother's understanding to be wise in the digital era by 25.11. The level of effectiveness of assistance is 59.44%, which means that the effectiveness of this assistance is in the moderate category. Mothers are the first school for their children, so the mother's perception of the concept of parenting from various perspectives is a benchmark for the success of a mother's parenting pattern.